Influence of preparation methods and thermal treatment in melt-solidified and cast films of poly(vinylidene fluoride-trifluorethylene) copolymers - Alves, Neri [UNESP]; Plepis, AMG; Giacometti, J. A.; Oliveira, O. N. (Gordon Breach Sci Publ Ltd, 1998)
This paper is aimed at addressing the differences observed in film properties when poly(vinylidene fluoride-trifluorethylene) P(VDF-TrFE) films are fabricated using distinct methods. Samples were obtained either from casting a solution or by compression molding from a molten phase and characterized by differential scanning calorimetry (DSC). It is shown that the main differences between melt-solidified and cast films arise from the thermal treatment inherent in the former samples.